Determinants in the adoption of alternate wetting and drying technique for rice production in a gravity surface irrigation system in the Philippines - Samoy-Pascual, Kristine; Yadav, Sudhir; Evangelista, Gio; Burac, Mary Ann; Rafael, Marvelin; Cabangon, Romeo; Tokida, Takeshi; Mizoguchi, Masaru; Regalado, Manuel Jose (MDPI, 2021)
Alternate Wetting and Drying (AWD) is a well-known low-cost water-saving and climate change adaptation and mitigation technique for irrigated rice. However, its adoption rate has been low despite the decade of dissemination in Asia, especially in the Philippines. Using cross-sectional farm-level survey data, this study empirically explored factors shaping AWD adoption in a gravity surface irrigation system. We used regression-based approaches to examine the factors influencing farmers’ adoption of AWD and its impact on yield. Results showed that the majority of the AWD adopters were farmers who practiced enforced rotational irrigation (RI) scheduling within their irrigators’ association (IA). With the current irrigation management system, the probability of AWD implementation increases when farmers do not interfere with the irrigation schedule (otherwise they opt to go with flooding). Interestingly, the awareness factor did not play a significant role in the farmers’ adoption due to the RI setup. However, the perception of water management as an effective weed control method was positively significant, suggesting that farmers are likely to adopt AWD if weeds are not a major issue in their field. Furthermore, the impact on grain yields did not differ with AWD. Thus, given the RI scheduling already in place within the IA, we recommend fine-tuning this setup following the recommended safe AWD at the IA scale.